Modulair-C redesign av kombiaggregat 500 ex - Johansson, Ludvig; Karlsson, Zack; Malmstedt, Emil; Olsson, Carl; Rehult, Edvin; Thim, Lovisa (My University, 2025)
This bachelor’s thesis was conducted in collaboration with ÅSS Processventilation with the objective of redesigning the central vacuum unit Kombiaggregat 500 EX. The current model suffers from outdated technology, poor user-friendliness, and a design language not aligning with the vision of the company. The aim of the project was to develop a modern, energy-efficient, and user-centered product with true Plug & Play functionality. Through pre-studies, user observations, and technical analysis several design concepts were generated and iteratively refined. The final solution features a maintenance-free cyclone separator, an improved filter system and a digital user interface. The unit has been redesigned both technically and aesthetically to enable easier installation, improved service ergonomics, and an enhanced user experience. The project also establishes the foundation for ÅSS’s future design language and product strategy.
Keywords: Processventilation; Cyklonfilter; Produktutveckling; Plug & Play; Användarcentrerad design